"Everybody just wants to do what's best for their child": Understanding how pro-vaccine parents can support a culture of vaccine hesitancy. Issue 48 (27th November 2015) - Wang, Eileen; Baras, Yelena; Buttenheim, Alison M.
Abstract: Background: Although a large majority of parents vaccinate their children, vaccine hesitancy has become more widespread. It is not well understood how this culture of vaccine hesitancy has emerged and how it influences parents' decisions about vaccine schedules. Objective: We sought to examine how attitudes and beliefs of parents who self-report as pro-vaccine are developed and contribute to immunization decisions, including delaying or spacing vaccines. Methods: Open-ended, in-depth interviews ( N  = 23) were conducted with upper-middle class parents with young children living in Philadelphia. Interview data were coded and key themes identified related to vaccine decision-making. Results: Parents who sought out vaccine information were often overwhelmed by the quantity and ambiguity when interpreting that information, and, consequently, had to rely on their own instinct or judgment to make vaccine decisions. In particular, while parents in this sample did not refuse vaccines, and described themselves as pro-vaccine, they did frequently delay or space vaccines. This experience also generated sympathy for and tolerance of vaccine hesitancy in other parents. Parents also perceived minimal severe consequences for deviating from the recommended immunization schedule. Conclusion: These findings suggest that the rise in and persistence of vaccine hesitancy and refusal are, in part, influenced by the conflicts in the information parents gather, making it difficult to interpret. Considerable deviations from the recommended vaccination schedule may manifest even within a pro-vaccine population due to this perceived ambiguity of available information and resulting tolerance for vaccine hesitancy.